Prevalence of anemia in Iranian athletes participating in the camps for selecting female national teams - Torkan, F.; Kabir, A.; Hakemi, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: Anemia is one of the most prevalent and preventable diseases that is more important (because of higher prevalence) in women. It has some complications related to the cardiovascular system, lung, brain, kidney and general body function if its diagnosis is delayed. Early diagnosis has a prophylactic effect on its complications and increases the physical and psychic abilities. This study determined the prevalence of anemia in female athletes to show the extent of anemia between them, and as the basis for increasing their performance by treatment. Methods: A descriptive cross-sectional study on 156 female athletes in camps for selecting national teams in 2001 was done by a census method. Medical history, physical examination and clinical data, the information was recorded by physicians. Descriptive indicators and tests such as chi-square, and correlation coefficients by SPSS 10.05 software were used in the analysis. Results: The mean age was 20.47(19.53-21.41) years old. 9.6% of athletes had hemoglobin (Hb) equal to or less than 11.5gr/dl, 17.3% of them had Hb less than 12 gr/dl and 57.7% of them had Hb less than 13 gr/dl. Percent of anemia and mean of Hb were the same in different athletes groups. 16.7% of them had hematocrit equal or less than 36%. Their red blood cell in 5.1% of them was less than 400000 per milliliter (ml). 5.8% had microcytosis and 6% had macrocytosis. 4.55 of them had hypochromia and 24.4% had MCHC<=32%. Discussion: Athletes tend to have lower hemoglobin concentrations than their sedentary counterparts (sports anemia). Sports anemia is a pseudo-anemia and a beneficial adaptation to aerobic exercise. Athletes, however, can also develop true anemia due to different causes such as iron deficiency, footstrike (exertional) hemolysis, sickle cell, beta thalassemia, bleeding, clotting problems, and nutritional disorders. Iron deficiency anemia (IDA) is the most common cause of true anemia in athletes with the prevalence in female athletes of 5%. Because of the high prevalence of anemia in our study we suggest evaluation for IDA, nutritional disorders, hemoglobinopathies, coagulopathies,and hemolysis for future researches.